Pediatric tracheostomy tube decannulation with or without polysomnography: A PRO‐CON debate. Issue 3 (12th January 2022) - Xiao, Lena; Kaspy, Kimberley; Zielinski, David; Amin, Reshma
Abstract: Determining the timing for decannulation in children with a tracheostomy is a complex process, as the appropriate timing varies based on the initial indication for the tracheostomy tube as well as individual patient characteristics. The original condition for which a tracheostomy was created may improve over time with decannulation being a very important long‐term goal for many families and multidisciplinary teams. However, decannulation is an inherently risky procedure associated with morbidity and mortality. Therefore, careful planning is required to ensure the safety of the procedure. Although routine airway endoscopy is an important component of decannulation protocols, guidelines are less prescriptive regarding the definition of a complete endoscopic airway evaluation and the routine use of polysomnography. This review will summarize the important PRO and CON arguments of integrating polysomnography into pediatric decannulation protocols.